Macrophage polarization and MRSA infection in burned mice. Issue 2 (15th November 2016) - Nishiguchi, Tomoki; Ito, Ichiaki; Lee, Jong O; Suzuki, Sumihiro; Suzuki, Fujio; Kobayashi, Makiko
Abstract : Mortality associated with Staphylococcus aureus infection remains high during the sub‐acute phase of burn injury. In this study, we aimed to improve antibacterial resistance of sub‐acutely burned mice through macrophage polarization. Sepsis did not develop in mice at the sub‐acute phase of 5% total body surface area (TBSA) burn after being infected with methicillin‐resistant S. aureus (MRSA), and M1 macrophages (interleukin (IL)‐10 − IL‐12 + inducible nitric oxide synthase + Mφ) were isolated from these mice. In contrast, predominantly M2b macrophages (C‐C motif chemokine ligand 1 (CCL1) + IL‐10 + IL‐12 − Mφ) were isolated from mice with >15% TBSA burn, and all of these mice died after the same MRSA infection. Comparing NOD scid gamma mice inoculated with Mφ with 25% TBSA burns, all mice treated with CCL1 antisense oligodeoxynucleotide (ODN) survived after MRSA infection, whereas all untreated mice given the same infection died within 4 days. CCL1 antisense ODN has been characterized as a specific polarizer of M2bMφ. M1Mφ were isolated from MRSA‐infected mice with 25% TBSA burn after treatment with CCL1 antisense ODN, and these mice were shown to be resistant against a lethal dose of MRSA infection. M1Mφ were also isolated from 25% TBSA‐burned mice infected with MRSA when the ODN was administered therapeutically, and subsequent sepsis was effectively controlled in these mice. These results indicate that the M2bMφ polarizer is beneficial for controlling MRSA infection in mice at the sub‐acute phase of severe burn injury.